Evidence for Up-Regulation of Purinergic Receptor Genes Associating with TRPV1 Receptors and Neurotrophic Factors in the Inflamed Human Esophagus - Shieh, K.-R.; Yang, S.-C.; Tseng, H.-L.; Yi, C.-H.; Liu, T.-T.; Chen, C.-L. (Current Molecular Medicine, 2014)
Purinergic receptors are implicated in nociceptive signaling in small primary afferents via activation of adenosine triphosphate (ATP). ATP appears to mediate HCl-induced transient receptor potential vanilloid receptor 1 (TRPV1) activation in esophageal mucosa. Up-regulation of TRPV1 expression in gastroesophageal reflux disease (GERD) is associated with increased nerve growth factor (NGF) and glial derived neurotrophic factor (GDNF). This study aims to genetically determine the expression of purinergic receptors in severe inflamed human esophagus. Distal esophageal biopsies from the subjects with erosive GERD, asymptomatic patients (AP) and healthy ones were examined. Using real-time qPCR for detecting purinergic receptors (P2X2, P2X3, P2X7, P2Y1, P2Y2, P2Y4, P2Y6 and P2Y12), TRPV1, TRPV4, NGF, and GDNF was done in this study. Both P2X3 and P2X7 mRNA expressions in GERD patients significantly increased than those in healthy controls (P < 0.001) and AP (P < 0.001), but P2X2, P2Y1, P2Y2, P2Y4, P2Y6, P2Y12 or P2Y12 had no difference within the control, AP or GERD subjects. The well correlated expression in P2X3 gene with TRPV1 (r = 0.46, P = 0.002), NGF (r = 0.54, P = 0.0002), and GDNF (r = 0.64, P = 0.0001) was found. The P2X7 gene expressions also well correlated with TRPV1 (r = 0.47, P = 0.002), NGF (r = 0.32, P = 0.037), and GDNF (r = 0.42, P = 0.005). These results suggest that chronic esophagitis increases mRNA expressions of P2X3 and P2X7 receptors accompanied by up-regulation of TRPV1 and neurotrophic factors (NGF and GDNF). These genetical alterations in esophageal mucosa might mediate sensitization of inflamed human esophagus.
Keywords: Acid reflux